Psychrophilic microorganisms: challenges for life - D'Amico, Salvino (2006)
The ability of psychrophiles to survive and proliferate at low temperatures implies that they have overcome key barriers inherent to permanently cold environments. These challenges include: reduced enzyme activity; decreased membrane fluidity; altered transport of nutrients and waste products; decreased rates of transcription, translation and cell division; protein cold-denaturation; inappropriate protein folding; and intracellular ice formation. Cold-adapted organisms have successfully evolved features, genotypic and/or phenotypic, to surmount the negative effects of low temperatures and to enable growth in these extreme environments. In this review, we discuss the current knowledge of these adaptations as gained from extensive biochemical and biophysical studies and also from genomics and proteomics.